2014
DOI: 10.1016/j.ydbio.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

PIWI proteins are essential for early Drosophila embryogenesis

Abstract: PIWI proteins, a subfamily of the ARGONAUTE/PIWI protein family, have been implicated in transcriptional and posttranscriptional gene regulation and transposon silencing mediated by small non-coding RNAs, especially piRNAs. Although these proteins are known to be required for germline development, their somatic function remains elusive. Here, we examine the maternal function of all three PIWI proteins in Drosophila; Piwi, Aubergine (Aub) and Argonaute3 (Ago3) during early embryogenesis. In syncytial embryos, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 33 publications
10
47
0
Order By: Relevance
“…4D; Supplemental Table S8). These include well-known examples such as Oskar (Osk), String (Stg), Piwi, Aubergine (Aub), Extra sexcombs (Esc), Dorsal (Dl), Mothers against dpp (Mad), and Swallow (Swa) (Chao et al 1991;Edgar and Datar 1996;Luschnig et al 2004;Simmons et al 2010;Mani et al 2014). However, also yet undescribed candidates like CG11674, CG5568, CG17018, CG15047, Zpg, GammaTub37C, and Tosca found in this set represent interesting candidates with a putative role in oogenesis and early embryogenesis.…”
Section: Maternally Loaded Proteinsmentioning
confidence: 86%
“…4D; Supplemental Table S8). These include well-known examples such as Oskar (Osk), String (Stg), Piwi, Aubergine (Aub), Extra sexcombs (Esc), Dorsal (Dl), Mothers against dpp (Mad), and Swallow (Swa) (Chao et al 1991;Edgar and Datar 1996;Luschnig et al 2004;Simmons et al 2010;Mani et al 2014). However, also yet undescribed candidates like CG11674, CG5568, CG17018, CG15047, Zpg, GammaTub37C, and Tosca found in this set represent interesting candidates with a putative role in oogenesis and early embryogenesis.…”
Section: Maternally Loaded Proteinsmentioning
confidence: 86%
“…Indeed, it has been shown that the depletion of maternal-effect genes, Zar1 and Zar1l, causes embryonic arrest in early mouse embryos (Wu et al 2003;Hu et al 2010). Moreover, lack of maternal Piwi protein in fly embryos causes developmental defects, such as abnormal chromosome morphology and cell cycle arrest (Mani et al 2014). One possibility is that these mRBPs (e.g., ZAR1 and Piwi) escaped detection in other mRNA interactome capture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…28). A recent publication has shown that all Drosophila PIWIs are expressed during early embryogenesis and that depletion of maternal Drosophila PIWIs results in profound chromosomal and mitotic defects, thus establishing a crucial function for PIWIs in the earliest stage of somatic development 29 . Together with the work on basal eukaryotes, studies in Drosophila highlight the existence and function of PIWIs in somatic tissues.…”
Section: Expression Of Piwis and Pirnas In Somatic Tissuesmentioning
confidence: 99%